USING GOOGLE DOCS ON COLLABORATIVE WRITING TECHNIQUE FOR TEACHING ENGLISH TO NON ENGLISH DEPARTMENT STUDENTS - Endry Sri Rahayu (Universitas Negeri Padang, 2016)
This study investigates the acceptance of Google Docs as the learning innovation for collaborative writing to non-English department students. The objective of this study is to discover the non-English Department Students’ perception of Google Docs as a new innovation tool to write collaboratively in English course. This descriptive qualitative study analyzed one of the new technologies, Google Docs as a tool for a challenge of the collaborative writing skill to the students. The study was out of classroom based, and the participants were 39 of non-English Department students. Students were also interviewed to discover their experience and responds using Google Docs. The result of the study showed that a Google Docs is an acceptable tool for learning innovation for collaborative writing especially for English course. Most of the students involved in this study thought that Google Docs is an effective teaching tool as the learning innovation for collaborative writing to Non English Department Students. Finally, it can be concluded that collaborative writing by using of Google Docs to non-English Department has numerous affective benefits such as can enhance student’s interest in learning writing, utilize a range social skills that help communication in the technological environment among the group, lower the anxiety associated with completing assignment alone, and raise the student’s confident in mastering English to their career readiness.